2015
DOI: 10.5039/agraria.v10i3a5132
|View full text |Cite
|
Sign up to set email alerts
|

Zinc fertilization as an alternative to increase the concentration of micronutrients in edible parts of vegetables

Abstract: Because nutrients consumed by human beings are derived from the soil-plant system, biofortification of the edible parts of horticultural crops can be a very useful technique for countering human malnutrition. The objective of this study is to evaluate the transfer of Zn from the soil to the edible parts of carrots, kale and okra in latosol treated with increasing doses of Zn. The experiment was conducted in a randomized block design with a 4 x 3 x 4 factorial scheme, consisting of four Zn doses (0, 50, 150, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Regarding the Mn contents, no effect of the spraying with zinc was observed. Despite that the observed results diverges from several studies that found antagonism between the two nutrients (Omtiaz et al, 2003;Hasani et al, 2012), the effect of zinc on Mn is not well understood and may vary between species (Lima et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding the Mn contents, no effect of the spraying with zinc was observed. Despite that the observed results diverges from several studies that found antagonism between the two nutrients (Omtiaz et al, 2003;Hasani et al, 2012), the effect of zinc on Mn is not well understood and may vary between species (Lima et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Several authors have reported a low relationship between Cu contents and applied Zn doses (Fageria, 2002;Mao et al, 2014). Lima et al (2015), working with carrots, okra and cabbage, and increasing doses of Zn applied to the soil, did not observe effect of Zn on leaf Cu contents. Regarding the Mn contents, no effect of the spraying with zinc was observed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since carrot is a food source of Fe, it becomes important to check any reduction of its content. In the study by Lima et al (2015), Zn levels found in carrot roots increased linearly, whereas a quadratic response was observed in relation to the Fe content in these plants; thus, it was also confirmed that, with application of increasing doses of Zn in the soil, there was a reduction of Fe content in the edible parts of carrot. Smical et al (2008) found that lettuce grown in soil with the addition of Zn (50 to 300 mg kg -1 ) had higher relative contents of Fe in the roots, supporting the natural variation of the plant in relation to preferential assignment of micronutrients to the roots, differing from that found in this study with carrots.…”
Section: Zinc Root Concentrationsupporting
confidence: 54%
“…The application of fertilizers with Zn has shown promising results, Pascoalino (2014) described an average increase of Zn concentration in wheat grains of 1.06 times compared with the control. Therefore, carrot has more potential for Zn biofortification compared with wheat, as this mineral remains more concentrated in the root and has greater difficulty in translocation to aerial parts (Lima et al, 2015).…”
Section: Zinc Root Concentrationmentioning
confidence: 99%